Implementation of an RTS Video Game for Windows 10 (PC) Using the Unity Game Engine - Barrientos, Alfredo (2023)
The video game industry has undergone one of the most significant transformations in recent times. This is reflected not only in the economic aspect but also in the increasing number of players who want to explore and interact in the world of video games in recent years. As for the Real-Time Strategy (RTS) genre, which reached its peak in the early 2000s, it did not continue to see the same trend in game development, and the population of active players has been declining [1]. The primary reason for this continuous decline is the competition from games in other genres such as First Person Shooter (FPS), Multiplayer Online Battle Arena (MOBA), and other genres with attractive characteristics that set them apart. In response to this, a solution is offered, which involves the development of a multiplayer RTS video game for Windows operating systems (PC), with the aim of generating greater interest among both beginner and expert players. This document will explain the procedures for the functional and aesthetic development of the video game, as well as validation regarding the user experience.